La inclusión educativa y la importancia en el manejo del aula dirigido a las docentes de educación inicial de la escuela “Republica de Colombia” en la provincia de Cotopaxi, en el cantón Saquisilí, parroquia Saquisilí en el año lectivo 2014-2015 - Guamaní Moncayo, Juliana de las Mercedes (2016)
The following work was developed in order to achieve social development, integration for each of the children with different abilities that which is intended to achieve socialization for that way each child is not excluded and thus the release of prejudice to each of the child with different capabilities. Family and institutions are important as this directly influence the development of each of the children with disabilities manner, so that educational inclusion in the "Republic of Colombia School" an educational tool is necessary for the teaching of early childhood education for classroom management so that in this way there is no discrimination towards each child with disabilities and seek methodological strategy as well teachers motivate and have a high self-esteem children but in the same way parents family are partakers to help them but the key element is the parent dialog teachers, is where born in workshops for improving classroom management in educational inclusion and thus exploit the capabilities of children.